PENGARUH RETURN ON ASSETS, DEBT TO ASSETS RATIO, DAN OPINI AUDIT TERHADAP AUDIT DELAY - Suarsa, Abin; Nawawi, Eki Muhamad (2018)
This research is performed in order to test the influence of the variable ROA, DAR and audit opinion toward Audit Delay to the company of manufactur sector basic industrial and chemical in BEI for periode 2013-2014 Analysis technique used is multi regression and hypothesis test use t-statistic to test coefficient of regression partial. The analyse result indicate that data ROA and Audit Opinion in partial significant toward Audit Delay. DAR in partial not significant toward Audit Delay. Anova test result show ROA, DAR and Audit Opinion in simultan significant toward AudIt delay.